INTEGRITAS KEPEMIMPINAN DALAM AL-QUR’AN TERHADAP PILKADA DAN PERMASALAHANNYA - Ahmad Zabidi (Jurnal Ilmiah Al-Muttaqin, 2021)
Leadership is an urgent issue in the order of community life, especially in regional elections (pilkada) is a party of democracy in the city or regional level that determines the direction of future government sustainability policy by capitalizing on the political parties that accompany it, so the election of regional heads (pilkada) raises many pro and cons among the people and the national political elite in addressing the problems and dynamics of a better, transparent, accountable and integrity government. So that the elections are expected not to satisfy power and ambition but solutions in building a just, prosperous and prosperous society based on the formulation of the Pancasila and the 1945 Constitution as the philosophy of the nation that uses a democratic system. Then the characteristic of democracy is freedom, equality, and people's sovereignty. Democracy is basically an understanding that wants freedom, sovereignty for the people in accordance with existing legal norms, so that democracy in political terms is defined as people's government.